Short-term heat acclimation improves the determinants of endurance performance and 5-km running performance in the heat - James, C. A.; Richardson, A. J.; Watt, P. W.; Willmott, A. G. B.; Gibson, O. R.; Maxwell, N. S. (Applied Physiology, Nutrition, and Metabolism, 2017)
This study investigated the effect of 5 days of controlled short-term heat acclimation (STHA) on the determinants of endurance performance and 5-km performance in runners, relative to the impairment afforded by moderate heat stress. A control group (CON), matched for total work and power output (2.7 W/kg), differentiated thermal and exercise contributions of STHA on exercise performance. Seventeen participants (10 STHA, 7 CON) completed graded exercise tests (GXTs) in cool (13 °C, 50% relative humidity (RH), pre-training) and hot conditions (32 °C, 60% RH, pre- and post-training), as well as 5-km time trials (TTs) in the heat, pre- and post-training. STHA reduced resting (p = 0.01) and exercising (p = 0.04) core temperature alongside a smaller change in thermal sensation (p = 0.04). Both groups improved the lactate threshold (LT, p = 0.021), lactate turnpoint (LTP, p = 0.005) and velocity at maximal oxygen consumption (vV?O2max; p = 0.031) similarly. Statistical differences between training methods were observed in TT performance (STHA, -6.2(5.5)%; CON, -0.6(1.7)%, p = 0.029) and total running time during the GXT (STHA, +20.8(12.7)%; CON, +9.8(1.2)%, p = 0.006). There were large mean differences in change in maximal oxygen consumption between STHA +4.0(2.2) mL/kg·min (7.3(4.0)%) and CON +1.9(3.7) mL/kg·min (3.8(7.2)%). Running economy (RE) deteriorated following both training programmes (p = 0.008). Similarly, RE was impaired in the cool GXT, relative to the hot GXT (p = 0.004). STHA improved endurance running performance in comparison with work-matched normothermic training, despite equality of adaptation for typical determinants of performance (LT, LTP, vVO2max). Accordingly, these data highlight the ergogenic effect of STHA, potentially via greater improvements in maximal oxygen consumption and specific thermoregulatory and associated thermal perception adaptations absent in normothermic training.